Behavior of flush end plate steel joints with sudden column removal - Udaya Pinasthikaswasti (2013)
The use of steel in building design is increasingly become more popular. Steel design provides a more ductile and robust structure, together with a more practical way of assembly method. All of these are made possible by the advanced construction technology and research. It is foreseen that the use of structural steel will be more favored in the future. Hence, more study needs to be done to ensure a better steel structure quality for future use.